PEMEROLEHAN NEGASI SEORANG ANAK DWIBAHASA INDONESIA-JERMAN PADA UMUR 1;2 SAMPAI 3;0 - Ni Luh Putu Sri Adnyani; I Nyoman Pasek Hadisaputra (Masyarakat Linguistik Indonesia, 2013)
The study aims at a) finding out the negation developed by the child between the age of 1;2 until 3;0, b) describing the steps of the development, and c) explaining the function of the negation produced by the child. This is a longitudinal qualitative research. The result of the study shows that the acquisition of negation follows a sequence pattern, based on the order of appearance; they are ndak/tidak, belum, jangan and bukan. Yet, the only negation produced in Deutsch is nein. The word nein was initially produced when Lila was 1;6 and has been frequently and productively used by the child. At the age of 1;8, Lila also started to use negation in Balinese such as de and sing nyak. The Balinese was acquired as a result of being in a peergroup. The function of the negation produced by the child are rejecting an offer or an activity, denying an existence of something, denying a certain knowledge, forbidding someone to do something, negating perfective and opposing.